2014
DOI: 10.1371/journal.pgen.1004507
|View full text |Cite
|
Sign up to set email alerts
|

KDM6 Demethylase Independent Loss of Histone H3 Lysine 27 Trimethylation during Early Embryonic Development

Abstract: The early mammalian embryo utilizes histone H3 lysine 27 trimethylation (H3K27me3) to maintain essential developmental genes in a repressive chromatin state. As differentiation progresses, H3K27me3 is removed in a distinct fashion to activate lineage specific patterns of developmental gene expression. These rapid changes in early embryonic chromatin environment are thought to be dependent on H3K27 demethylases. We have taken a mouse genetics approach to remove activity of both H3K27 demethylases of the Kdm6 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 75 publications
7
106
1
Order By: Relevance
“…These cell types are unique in that they can be 65 identified and reliably collected from whole testes in multiple mammalian species without the 66 use of transgenes or genetic markers (see Methods). In addition, they differ substantially from 67 each other in their place in the cell cycle and in the physical state of their chromatin: pachytenes 68 are tetraploid cells in meiotic prophase, with large nuclei and synapsed pairs of homologous 69 chromosomes, while round spermatids are haploid cells that have completed meiosis and have 70 small, compact nuclei. Inclusion of both cell types in our study allowed us to control for the 71 effects of chromatin compaction and physical state of the nucleus during spermatogenic 72 development.…”
mentioning
confidence: 99%
“…These cell types are unique in that they can be 65 identified and reliably collected from whole testes in multiple mammalian species without the 66 use of transgenes or genetic markers (see Methods). In addition, they differ substantially from 67 each other in their place in the cell cycle and in the physical state of their chromatin: pachytenes 68 are tetraploid cells in meiotic prophase, with large nuclei and synapsed pairs of homologous 69 chromosomes, while round spermatids are haploid cells that have completed meiosis and have 70 small, compact nuclei. Inclusion of both cell types in our study allowed us to control for the 71 effects of chromatin compaction and physical state of the nucleus during spermatogenic 72 development.…”
mentioning
confidence: 99%
“…In contrast, various lineage establishments require KDM6A protein but not its demethylase activity of KDM6A, including embryonic stem cell differentiation, Caenorhabditis elegans development, and early embryonic development (10,49,50). The role of KDM6A in regulating gene expression, aside from demethylating histones, is still not understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, part of the GSK-J4 effect has to involve H3K27 methylation as we see attenuation of treatment effects in differentiating Eed-KO ESCs. Recently, Shpargel et al have reported that KDM6A KDM6B double-KO embryos can develop to term and that repressed genes lose H3K27 methylation and are then expressed (Shpargel et al, 2014). The strategy used in the approach by Shpargel et al involved the deletion of KDM6B exons 14-21.…”
Section: Discussionmentioning
confidence: 99%